Moses As Figure of the Pope: II. A Christological-political topos, from Eugenius IV to Clement VII - Lettieri, Gaetano (De Medio Aevo, 2023)
Between the 15th and the 16th century, the Popes who emerged from the Western Schism and went through the conciliarist conflicts promoted their symbolic identification with Moses, a spiritual and temporal monarch, endowed with prophetic and imperial/legislative authority. Thus, Moses was not a generic symbol of the "Renaissance man" leaning towards divinization, but rather a specific and traditional figure of the Pope, the sole holder of full divinely founded sovereignty, the absolute sacred head and supreme earthly princeps, whose imperatoria maiestas encompasses supreme theological iustitia, the foundation and source of the leges, and the sacred possession of arma, the instrument of protection and glorification of the civitas Dei on earth. Here I will schematically give some examples of the most eloquent and significant points of this trajectory, bringing into focus the relevance and pervasiveness of humanistic-Renaissance Papal ideology.